2003
DOI: 10.1128/aem.69.7.4192-4199.2003
|View full text |Cite
|
Sign up to set email alerts
|

Saprotrophic and Mycoparasitic Components of Aggressiveness of Trichoderma harzianum Groups toward the Commercial Mushroom Agaricus bisporus

Abstract: We examined the mycoparasitic and saprotrophic behavior of isolates representing groups of Trichoderma harzianum to establish a mechanism for the aggressiveness towards Agaricus bisporus in infested commercial compost. Mycoparasitic structures were infrequently observed in interaction zones on various media, including compost, with cryoscanning electron microscopy. T. harzianum grows prolifically in compost in the absence or presence of A. bisporus, and the aggressive European (Th2) and North American (Th4) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 51 publications
2
45
0
1
Order By: Relevance
“…It has been previously shown that A. bisporus metabolites increase the rate of extension of T. aggressivum hyphae (Muthumeenakshi et al 1998) and that and saprotrophic growth in mushroom compost is key to its survival strategy (Williams et al 2003). The re-arrangement of the actin cytoskeleton may be an aspect of both of these behaviours.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been previously shown that A. bisporus metabolites increase the rate of extension of T. aggressivum hyphae (Muthumeenakshi et al 1998) and that and saprotrophic growth in mushroom compost is key to its survival strategy (Williams et al 2003). The re-arrangement of the actin cytoskeleton may be an aspect of both of these behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…This may be partly due to the fact that the fungus was grown under non-inducing conditions. Previous studies have shown the secretion of fungal cell wall associated depolymerising enzymes by T. aggressivum in the presence of A. bisporus (Williams et al 2003;Guthrie & Castle 2006) and the production of these enzymes is considered to be indicative of mycoparasitic activity. However, in both studies the depolymerising enzymes were secreted into the extracellular space of T. aggressivum and so it may be that these proteins are insensitive to change or are present in relatively low abundance in the intracellular protein fraction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations